2003
DOI: 10.1111/j.1741-3729.2003.00258.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Protective Factors in Young Children's Adjustment to Parental Divorce: A Review of the Research

Abstract: This article reviews the literature on parental divorce and early childhood development, using developmental psychopathology as an organizing framework. With respect to young children, three questions are addressed: How does parental divorce affect developmental outcomes? What risk and protective factors influence adaptation? How does early parental divorce affect later adjustment? Because this review is unique in its focus on divorce-related issues specific to young children, limitations of existing research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
22

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 60 publications
2
30
0
22
Order By: Relevance
“…Additionally, it is possible that the observed relation reflects confounding by parental psychopathology, since parental divorce or separation is associated with a greater likelihood of depression among parents, and parental depression is related to depression in offspring (Spence et al, 2002;Wood et al, 2004). Higher levels of parental support were associated with lower levels of depressive symptoms in this analysis, independent of the marital status of the parents, which is consistent with other studies that have found a strong protective role of support from both custodial and non-custodial parents in predicting children's internalizing and externalizing behaviors (King & Sobolewski, 2006;Leon, 2003).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Additionally, it is possible that the observed relation reflects confounding by parental psychopathology, since parental divorce or separation is associated with a greater likelihood of depression among parents, and parental depression is related to depression in offspring (Spence et al, 2002;Wood et al, 2004). Higher levels of parental support were associated with lower levels of depressive symptoms in this analysis, independent of the marital status of the parents, which is consistent with other studies that have found a strong protective role of support from both custodial and non-custodial parents in predicting children's internalizing and externalizing behaviors (King & Sobolewski, 2006;Leon, 2003).…”
Section: Discussionsupporting
confidence: 81%
“…Our study suggests that, consistent with some prior work (Gilman et al, 2003), the family environment may influence depressive symptoms over and above its association with family income. The effect of the family environment, particularly with regard to parental divorce or separation, on depression may stem from exposure to prolonged conflict between custodial and non-custodial parents (Amato & Keith, 1991;Amato, 2000), less positive parenting and parental attention in divorced or separated families (Black & Pedro-Carroll, 1993;McLeod & Shanahan, 1993), or conflict with parents or new step-parents after the divorce (Aseltine, 1996;Leon, 2003). Additionally, it is possible that the observed relation reflects confounding by parental psychopathology, since parental divorce or separation is associated with a greater likelihood of depression among parents, and parental depression is related to depression in offspring (Spence et al, 2002;Wood et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, recently conflicting results have been shown [49]. Joint physical custody is supposed to be decided upon and arranged by the parents for the good of the child [19,31,50]. If the parents cannot agree, courts may impose the terms of joint physical custody, in which case neither the children nor the parents choose the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Great strain is placed upon children living amid serious parental conflict. These children are at increased risk of psychiatric, behavioral, and school-related problems (Kelly & Emery, 2003;Leon, 2003). Long-term custody battles can lead to mental health problems for the children, even after they have become adults (Johnston, Roseby, & Kuehnle, 2009;Stewart, 2000).…”
Section: Introductionmentioning
confidence: 99%